2013
DOI: 10.1099/vir.0.052092-0
|View full text |Cite
|
Sign up to set email alerts
|

Four novel papillomavirus sequences support a broad diversity among equine papillomaviruses

Abstract: Papillomaviruses appear to be species-specific pathogens, and it was suggested that each animal species might harbour its own set of papillomaviruses. However, all approaches addressing the underlying evolutionary phenomena still suffer from very limited data about animal papillomaviruses. In case of the horse for example, only three equine papillomaviruses (EcPVs) have been identified. To further address the situation in this host, suspected papillomavirusassociated lesions were tested for EcPV DNA. Four nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 34 publications
6
77
0
1
Order By: Relevance
“…More than 150 different human‐specific papillomavirus types (HPVs) have been described, and the discoveries of recent years indicate that several animal species carry diverse sets of specific papillomaviruses as well . Horses are one of those species, and to date, seven different equus caballus papillomavirus types (EcPVs) are known . Furthermore, the two bovine types, BPV1 and BPV2, can infect equids and are associated with equine sarcoids .…”
Section: Introductionmentioning
confidence: 99%
“…More than 150 different human‐specific papillomavirus types (HPVs) have been described, and the discoveries of recent years indicate that several animal species carry diverse sets of specific papillomaviruses as well . Horses are one of those species, and to date, seven different equus caballus papillomavirus types (EcPVs) are known . Furthermore, the two bovine types, BPV1 and BPV2, can infect equids and are associated with equine sarcoids .…”
Section: Introductionmentioning
confidence: 99%
“…Estadual Paulista, Botucatu, SP Equine aural plaques were recently associated with four equine papillomaviruses (EcPVs) (Lange et al, 2013;. These viruses have been detected in fresh samples by PCR (Lange et al 2013;, but EcPVs have not been identified in formalinfixed and paraffin-embedded (FFPE) aural plaque samples.…”
mentioning
confidence: 99%
“…Estadual Paulista, Botucatu, SP Equine aural plaques were recently associated with four equine papillomaviruses (EcPVs) (Lange et al, 2013;. These viruses have been detected in fresh samples by PCR (Lange et al 2013;, but EcPVs have not been identified in formalinfixed and paraffin-embedded (FFPE) aural plaque samples. Archives of FFPE aural plaques and other papilloma specimens stored in diverse veterinary diagnostic centers may represent a valuable source of material for the etiologic diagnosis of papillomaviruses involved in the disease (Newkirk et al, 2014); therefore, the aim of this study was to optimize a reliable method for the detection of the EcPVs in FFPE aural plaque samples by PCR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Papillomas are common equine neoplasms that affect several cutaneous sites, as well as oral, ocular and genital mucous membranes [1][2][3][4][5][6]. To date, almost 200 distinct papilloma viruses have been cloned, sequenced, and allocated to various genera, including seven viruses termed EcPV1-7 that were identified in equine papillomas [7][8][9].…”
Section: Introductionmentioning
confidence: 99%